“Generación de indicadores dinámicos e interactivos para la toma de decisiones en las funciones sustantivas de la Facultad de Ciencias Administrativas y Económicas de la Universidad Técnica de Cotopaxi “. - Loja Veloz, Kevin Paul (2024)
In the Administrative and Economic Sciences Faculty of the Technical University of Cotopaxi, a critical need to implement a specialized solution in business intelligence and integrated dashboard that allows managing its academic and management indicators was detected. The growing volume of data, the dispersion in multiple sources, and the lack of automated analytical processing methods hindered the monitoring, traceability between substantive functions, and the analysis capacity required for informed decision making. To face this problem, the project proposed the development of a comprehensive indicator system, under an agile approach focused on the user, to facilitate the authorities and managers in governing the faculty. After a rigorous analysis of requirements with the main actors of the substantive functions, a database that integrates and organizes data from the different transactional systems was built. On the top of this unified data layer, powerful analytical exploitation functionalities and interactive visualizations through customized dashboards according to the role were implemented.